Socio-cultural change among the Penans of Kampong Tanjong Belipat, Batu Niah: A study conducted in Sarawak / Josephine Yaman - Josephine , Yaman (1979)
The introduction discusses the aim, scope and significance of the study, the background of the field of study, the methodology used and the problems encountered in the process of carrying out the research. Chapter I introduces the evolutionary theories in general and their applicability in the discussion of the socio-cultural change within the Tanjong Belipat Penan society. It also discusses the studies done and the problems relating to the Punan-Penan Question. Chapter II gives an account of the historical background of the Tanjong Belipat Penans and discusses the changes within the structure of dwellings and the settlement pattern. Chapter III discusses the changes within the kinship and family system while chapter IV gives an account of the past and the present economic activities of the Tanjong Belipat Penans. Chapter V discusses the changes within the religious and beliefs systems of the Tanjong Belipat Penans. Chapter VI discusses the changes within the administrative organization and the role of the leader in the Tanjong Belipat Penan context. The conclusion attempts to indentify the agents of change and tho degree of socio-cultural changes within the Tanjong Belipat Penan society.